2010
DOI: 10.1111/j.1476-5381.2010.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity therapy reacts to astrocyte GluA1 receptor upregulation following spinal cord injury

Abstract: For almost three decades intrathecal baclofen therapy has been the standard treatment for spinal cord injury spasticity when oral medication is ineffective or produces serious side effects. Although intrathecal baclofen therapy has a good clinical benefit-risk ratio for spinal spasticity, tolerance and the life-threatening withdrawal syndrome present serious problems for its management. Now, in an experimental model of spinal cord injury spasticity, AMPA receptor blockade with NGX424 (Tezampanel) has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…AMPA receptor subunits have been found on spinal α-motoneurons as well as on presynaptic Ia afferents, consistent with their demonstrated role in motor function. It has been shown that the expression of AMPA receptors can affect the clinical signs of spasticity and rigidity following cerebral ischemia; the intrathecal or systemic delivery of the selective AMPA receptor antagonist, NGX424, represents an effective therapy for modulating chronic spasticity in baclofen-tolerant animals (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…AMPA receptor subunits have been found on spinal α-motoneurons as well as on presynaptic Ia afferents, consistent with their demonstrated role in motor function. It has been shown that the expression of AMPA receptors can affect the clinical signs of spasticity and rigidity following cerebral ischemia; the intrathecal or systemic delivery of the selective AMPA receptor antagonist, NGX424, represents an effective therapy for modulating chronic spasticity in baclofen-tolerant animals (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…41,[61][62][63] Specifically, the alpha-2 adrenoceptor agonist clonidine has been shown not only to restore inhibition of CR activity after SCI but also to facilitate TA muscle activation during gait, 64 supporting the hypothesis that adequate CR control improves residual motor function. We believe that careful CR testing should be used to benchmark standard and new pharmacological strategies for the control of the SCI spasticity syndrome, 63,65,66 while examining the wider effect of these therapies on residual muscle function after SCI 40,41 Limitations and future studies No correlation was identified between Pl-TA CR activity and the grade of hypertonia or spasm frequency, perhaps reflecting the poor sensitivity of the modified Ashworth and Penn scales to detect flexor reflex activity. Measurement of spasm activity in clinical studies is usually performed with the Penn scale, 35 but this scale often fails to correlate with the underlying pathophysiological mechanisms of SCI spasticity syndrome during movement, 7 or indeed with CR activity in general.…”
Section: Discussionmentioning
confidence: 84%
“…Taken together these symptoms interfere with successful rehabilitation of residual voluntary motor function following incomplete spinal cord injury [ 31 ] and lead to lower quality of life [ 25 , 27 32 ]. Due to the multiple spinal pathophysiological mechanisms triggered by SCI, novel treatments should be designed to control neuroinflammation and promote growth of residual descending control systems across the lesion [ 33 38 ]. In this context, some symptoms of sensorimotor dysfunction following SCI have been related to glial reactivity at the injury site [ 39 , 40 ], while the restoration of constitutive serotonin and noradrenaline receptors has been reported to be essential for restoring residual motor function [ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%